Full-Scale linear cutting tests using a button cutter and deterministic performance prediction modeling for raise boring machines. (September 2022) - Shaterpour-Mamaghani, Aydin; Copur, Hanifi; Gumus, Arif; Tumac, Deniz; Balci, Cemal; Erdogan, Tayfun; Dogan, Engin; Kocbay, Ayhan
Graphical abstract: Highlights: Full-scale linear cutting tests are performed on the five block samples. Cutting characteristics of one single row (slice) button cutter are investigated. Physical-mechanical properties are correlated with the linear cutting test results. Two deterministic approaches are suggested to predict the performance of RBM. Abstract: The current study is an attempt to investigate the applicability of full-scale linear rock cutting tests (displacement controlled) and deterministic approaches to predict performance of raise boring machines (RBMs). Operational and performance parameters of the RBMs are recorded during field visits of Balya Lead-Zinc Underground Mine and Yusufeli Dam and HEPP Project in Turkey; then, five different block samples of rocks are obtained from the project sites. Full-scale linear cutting tests are performed on these samples with a 305 mm (12 in.) diameter button (kerf) cutter having an insert tip width of 11 mm. The cutter used in the tests is only a single slice of the real-life multi-row button cutter that is the slice taken from the middle (with an average diameter) and it looks like a single disc cutter with tungsten carbide inserts. Experimental studies indicate that cutting action of an RBM can be reliably simulated by full-scale linear cutting test. Suggested direct and indirect deterministic approaches predict reliably unit penetration and instantaneous penetration rates of RBMs. Uniaxial compressive strength and Brazilian tensile strength of the rocks are the most important parameters for predicting linear cutting performance parameters. This study could be further developed by adding cutting results of different rocks, field performance data, and developing an RQD or the rock mass fracturing correction factor. An improvement is especially required for prediction of the reamerhead thrust and torque parameters.